Great companies see employees as investments not human capital - Russo, David (FTPress Delivers, 2010)
"This Element is an excerpt from 17 Rules Successful Companies Use to Attract and Keep Top Talent: Why Engaged Employees Are Your Greatest Sustainable Advantage (ISBN: 9780137146703) by David Russo. What "human capital" really means--and why understanding it properly can help you unlock immense competitive advantage"--Resource description page.